A Brief Review on Phytoconstituents and Ethnopharmacology of Scoparia Dulcis Linn. (Scrophulariaceae) - Manas Ranjan Mishra,; R.K. Behera,; S. Jha,; A. Mishra,; D.K. Pradhan,; P.R. Choudary, (International Journal of Phytomedicine, 2011)
Scoparia dulcis Linn.(S. dulcis)or sweet broom weed commonly known as Mithipatti and Bana Dhania in Western Orissa, it is also known as ‘GhodaTulsi’in Hindi. The present review attempts to narrate the chemical constituents of S.dulcis and their uses. S.dulcis is rich in flavones, terpenes and steroids. Main chemical constituents such as scoparic acid A-C, scopadulcic acid A and B, scopadulciol, scopadulin and ammelin have been shown to contribute to the observed medicinal effect of the plant. In this review we have composed the structure and functions of those active ingredients with their melting point and other physical properties individually.Some aspects of the several speculated pharmacological properties of S. dulcis have been validated by scientific research, which includes the presence of hypoglycaemic and antitumour promoting compound. It also has antimicrobial and antifungal effects as well as antihyperlipidemic action.